RESEARCH ON FATIGUE CRACK PROPAGATION BEHAVIOR AND LIFE PREDICTION OF WIND TURBINE GEAR - YANG WenMeng; JIANG Wei; WANG Jie (Jixie qiangdu)
Gearbox is one of the core components of wind turbine, and the gear under heavy load is prone to fatigue fracture, which affects the normal operation of the generator. In this paper, the planetary-sun gear in the gearbox of 1.5 MW wind turbine is taken as the research object, and the finite element analysis model of fatigue crack propagation in the meshing process of gear pair is established through the joint programming of MATLAB and ABAQUS. The NASGRO equation is used to predict the residual fatigue life, and the influence of load and initial crack length on the fatigue crack propagation path and life is studied. The analysis results show that the simulation results of crack growth path based on the numerical model are in good agreement with the fatigue test results. At the same time, the meshing state of gear has a significant effect on the crack growth rate; the initial crack length has little effect on the crack growth path; the load amplitude will change the crack growth law under different meshing states, and the crack length and growth life will decrease with the increase of load.